Application of Growth Hormone in in vitro Fertilization - Xu, Yue-Ming; Hao, Gui-Min; Gao, Bu-Lang (Frontiers in Endocrinology, 2019)
As a peptide hormone secreted mainly by the anterior part of the pituitary gland in a pulsatile manner, growth hormone (GH) plays a critical role in cell growth, development and metabolism throughout the body. GH is a pleiotropic hormone with multifunctional effects ranging far beyond the effect on linear growth. Human oocytes and cumulus cells have GH receptors and can be directly influence by GH, and GH can promote nuclear maturation of denuded human oocytes. GH may also have an indirect effect on improving oocyte quality through activating synthesis of insulin-like growth factor (IGF)-I or promoting follicle-stimulating hormone-induced ovarian steroidogenesis. GH is involved in the regulation of female and male infertility and has consequently been applied in the management of infertility for many years, especially in females with poor ovarian response or poor prognosis. During ovarian stimulation, GH administration can improve the success rate of in vitro fertilization (IVF) probably through the beneficial effects of GH on oocyte quality as indicated by a higher number of oocytes and embryos arriving at the transfer stage and a higher fertility rate in GH-treated women. Pregnancy, implantation and live birth rates can all be increased by ovarian costimulation with GH, and the clinical pregnancy and live birth rates have been proved to be significantly increased by GH administration for controlled ovarian stimulation among patients with poor ovarian responses. However, there is still great controversy in the application of GH in IVF, and this review summarized recent advancements in the application of GH in IVF.